Bioactive components and anti-diabetic properties of Moringa oleifera Lam. Issue 14 (6th August 2022) - Wang, Fang; Bao, Yifan; Zhang, Chen; Zhan, Libin; Khan, Washim; Siddiqua, Sahifa; Ahmad, Sayeed; Capanoglu, Esra; Skalicka-Woźniak, Krystyna; Zou, Liang; Simal-Gandara, Jesus; Cao, Hui; et al.
Abstract: Moringa oleifera Lam. is a perennial tropical deciduous tree with high economic and pharmaceutical value. As an edible plant, M. oleifera Lam. is rich in nutrients, such as proteins, amino acids, mineral elements and vitamins. Besides, it also contains an important number of bioactive phytochemicals, such as polysaccharides, flavonoids, alkaloids, glucosinolates and isothiocyanates. M. oleifera for long has been used as a natural anti-diabetic herb in India and other Asian countries. Thus, the anti-diabetic properties of Moringa plant have evolved highly attention to the researchers. In the last twenty years, a huge number of new chemical structures and their pharmacological activities have been reported in particularly the anti-diabetic properties. The current review highlighted the bioactive phytochemicals from M. Oleifera . Moreover, evidence regarding the therapeutic potential of M. oleifera for diabetes including experimental and clinical data was presented and the underlying mechanisms were revealed in order to provide insights for the development of novel drugs.